Pediatric Balint’s Syndrome Variant: A Possible Diagnosis in Children - Swetha Sara Philip; Sunithi Elizabeth Mani; Gordon N. Dutton (Case Reports in Ophthalmological Medicine)
Balint’s syndrome is well described in adults, but not in children. It is caused by bilateral posterior parietal lobe damage and comprises a triad of simultanagnosia (inability to simultaneously see more than a small number of items), optic ataxia (impaired visual guidance of movement of the limbs and body), and apraxia of gaze (inability to volitionally direct gaze despite the requisite motor substrate) often associated with homonymous lower visual field loss. We, here, describe five children (four males, one female; mean age 7.4 years, [range 4−11 years]; birth weight ≤ 2.5 kg; four were born ≤ 36 weeks of gestational age and one at 40 weeks) who presented to the Cerebral Visual Impairment Clinic at a tertiary care center in South India with clinical features remarkably consistent with the above description. In all children neuroimaging showed bilateral parietooccipital gliosis with regional white matter volume loss and focal callosal thinning, consistent with perinatal hypoxic ischemic encephalopathy and possible neonatal hypoglycemia.